A Comparison of Full and Split Thickness Skin Grafts in Radial Forearm Donor Sites - Davis, Wellington J., III; Wu, Cindy; Sieber, David; Vandevender, Darl K. (Journal of Hand and Microsurgery, 2011)
To formally evaluate the functional and aesthetic outcomes between full versus split thickness skin graft coverage of radial forearm free flap donor sites. A retrospective chart review of 47 patients who underwent pedicled or free radial forearm free flap reconstruction from May 1997 to August 2004 was performed. Comparisons were made between patients who had donor site coverage with split thickness skin grafts (STSG) or full thickness skin grafts (FTSG). There was no statistically significant difference between the STSG and FTSG in the number of post-operative dressings, incidence of tendon exposure, time to healing at the skin graft donor site, and time to healing at the skin graft recipient site. The questionnaire data showed there was a trend toward higher scores with the radial forearm scar aesthetics and satisfaction in the FTSG group. Full thickness skin graft coverage of radial forearm free flap donor site is superior to split thickness skin graft coverage in terms of aesthetic outcome, and has no statistically significant difference in terms of tendon exposure, time to healing at the skin graft donor site, time to healing at the skin graft recipient site, or post operative pain.
Keywords: Radial forearm donor sites; Radial forearm flaps; Full thickness skin grafts; Split thickness skin grafts; Skin graft donor sites